An Inexpensive Autonomous Mobile Robot for Undergraduate Education: Integration of Arduino and Hokuyo Laser Range Finders - Ueyama, Yuki; Sago, Takashi; Kurihara, Toru; Harada, Masanori (IEEE access, 2022)
This paper discusses how to integrate a widely used, inexpensive laser range finder (LRF), the Hokuyo URG-04LX-UG01, with an easy-to-use Arduino microcontroller, into a science, technology, engineering, and mathematics (STEM) program for mechanical engineering students. The LRF has been used in several autonomous robots, in conjunction with laptops and desktop computers, due to its low cost. In addition, Arduino microcontrollers are suitable for educational purposes due to their open-source design and cost-effectiveness. Thus, combining the Hokuyo LRF with Arduino microcontrollers seems to be the best option to teach mechatronics to undergraduate students majoring in non-electrical and electronic engineering subjects, such as mechanical engineering. However, they have seldom been integrated for use in STEM education. Here, we built an autonomous robot integrating these devices and designed a course that teaches several aspects of mechatronics, including control engineering, programming, and embedded systems. The course for mechanical engineering students is 10 weeks in duration, easy to implement, and has a high cost-benefit ratio given the low cost of the robot (~1,350 USD). The results of a questionnaire given to the student participants upon completion of the course indicated that the course enhanced their knowledge, motivation, interest, and satisfaction. Therefore, we believe that this report will be helpful in providing a STEM education framework that allows students to acquire the basic skills and knowledge necessary to solve real-world problems.